Pétain : Verdun to Vichy - Bruce, Robert B. (Robert Bowman), 1963- (Potomac Books, 2008)
Analyzes the military career of one of the greatest, yet controversial, French military commanders of the twentieth century.
Keywords: Pétain, Philippe, -- 1856-1951.; France. -- Armée -- Biography.; Petain, Philippe, -- 1856-1951.; France. -- Armée -- Biographies.; Pétain, Philippe, -- 1856-1951; France. -- Armée; Pétain, Philippe.; Marshals -- France -- Biography.; Heads of state -- France -- Biography.; France -- History, Military -- 20th century.; France -- Politics and government -- 20th century.; Chefs d'État -- France -- Biographies.; France -- Histoire militaire -- 20e siècle.; France -- Politique et gouvernement -- 20e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Europe -- France.; Heads of state; Marshals; Politics and government; France; 1900-1999; collective biographies.; Biographies; Military history; Biographies.